Polyolefin graft copolymer with a reactive shell, method of preparation and use thereof
Patent Information
- Application Number
- CN202611169735.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-23
AI Technical Summary
然而,该物理共混体系存在固有缺陷:弹性体与刚性填料之间、填料与聚烯烃基体之间界面结合弱,导致“增韧不增强”或“增强不增韧”的矛盾
功能一体化与协同增强:本发明产物将柔性增韧相(PBA)和反应性界面层(GMA-co-BA)通过化学键集成于聚烯烃主链。应用于聚烯烃/无机填料体系时,PBA内层直接增韧基体,GMA-co-BA外层通过环氧基团与填料强效键合。这种结构实现了增韧与界面增强的分子级协同,使复合材料冲击强度和拉伸强度同时大幅提升。独特的界面缓冲层:壳层从内到外模量增加的结构,能在刚性填料与柔性聚合物基体之间形成理想的应力缓冲与传递过渡区,高效消散冲击能量,抑制界面脱粘和裂纹扩展。补强效应:无机填料通过化学键锚定在GMA-co-BA外层,可作为PBA柔性链段的物理交联点,限制其过度滑移,从而在赋予高韧性的同时,显著提升复合材料的强度、模量和耐热性,实现对橡胶相的原位补强。
Smart Images

Figure CN122958660A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an ultra-high molecular weight polyethylene fiber and its preparation method, and more specifically to a polyolefin graft copolymer with a reactive shell, its preparation method and its application, belonging to the field of high-performance fiber material manufacturing and surface modification technology. Background Technology
[0002] Polyolefin materials such as polypropylene (PP) and polyethylene (PE) are widely used due to their excellent comprehensive properties and low cost, but their inherent brittleness limits their application in structural components. Blending elastomers (such as POE) with rigid inorganic particles (such as nano-calcium carbonate) is a common toughening and reinforcing method. However, this physical blending system has inherent defects: weak interfacial bonding between the elastomer and the rigid filler, and between the filler and the polyolefin matrix, leading to the contradiction of "toughening without strengthening" or "reinforcing without toughening." While commonly used reactive compatibilizers (such as PP-g-MAH) can improve interfacial adhesion, they themselves lack structural toughening capabilities and have limited direct contribution to the toughness of composite materials.
[0003] For polyolefins such as polyethylene, due to their higher nonpolarity and lower surface energy, the modification effect of traditional compatibilizers on the interface between them and inorganic fillers is more limited. Therefore, developing a novel polymer structure that can integrate toughening and interfacial compatibilization functions at the molecular level and achieve a smooth modulus transition between the filler and the matrix is of great significance for preparing polyolefin composites with both high toughness and high strength. Summary of the Invention
[0004] This invention addresses the problems and shortcomings of existing technologies by providing a polyolefin graft copolymer with a reactive shell, its preparation method, and its applications. This polyolefin graft copolymer with a reactive shell possesses a shell structure of "flexible inner layer - gradient transition outer layer," which can simultaneously serve as an internal toughening phase and a highly efficient interfacial compatibilizer, thereby synergistically improving the toughness and strength of polyolefin composites. It can be applied to the preparation of high-toughness, high-strength polyolefin composites. When applied to polyolefin / inorganic filler systems, it can significantly improve both the impact strength and tensile strength of the composite material. Furthermore, the preparation method is simple, easy to implement, and operates under mild conditions with low cost.
[0005] This invention is achieved through the following technical solution: The polyolefin graft copolymer with a reactive shell of the present invention has the following general structural formula: PO-g-{PBA-g-(GMA-co-BA)}; wherein, PO is a polyolefin backbone, one or a combination of polypropylene and polyethylene; PBA is a polybutyl acrylate segment constituting the flexible inner layer of the shell; GMA-co-BA is a random copolymer segment of glycidyl methacrylate and butyl acrylate constituting the reactive outer layer of the shell; from the PBA segment to the GMA-co-BA segment, the relative content of the glycidyl methacrylate structural unit gradually increases, so that the modulus of the shell shows a gradient change that gradually increases from the inside to the outside; based on 100 parts by mass of the polyolefin backbone, the total grafting rate of the PBA segment and the GMA-co-BA segment is 50 to 100 parts by mass; g represents "grafting".
[0006] A further technical solution of the above-mentioned polyolefin graft copolymer with reactive shell of the present invention is that the mass ratio of PBA segment to GMA-co-BA segment is 5:1 to 10:1.
[0007] A further technical solution of the above-mentioned polyolefin graft copolymer with reactive shell of the present invention may be that the molar ratio of glycidyl methacrylate to butyl acrylate in the GMA-co-BA segment is 2:1 to 1:1.
[0008] The method for preparing the above-mentioned polyolefin graft copolymer with a reactive shell according to the present invention includes the following steps: S1. Preparation of PO-Cl, a polyolefin macromolecular initiator with C-Cl bonds on its surface; S2. Using the PO-Cl as an initiator, a surface-initiated atom transfer radical polymerization method is adopted to first initiate the butyl acrylate monomer to undergo a first polymerization reaction to form PBA segments; S3. Without terminating the reaction system, a mixture of butyl acrylate and glycidyl methacrylate monomers is added to the system to carry out a second polymerization reaction, thereby forming GMA-co-BA copolymer segments at the ends of the PBA segments to obtain a polyolefin graft copolymer with a reactive shell.
[0009] The preparation method of the above-mentioned polyolefin graft copolymer with reactive shell of the present invention is further described in the following method for preparing polyolefin macromolecular initiator PO-Cl with C-Cl bonds on the surface: under acidic conditions, sodium hypochlorite is used to react with polyolefin powder in a chlorination reaction; when the polyolefin powder is polypropylene powder, the reaction temperature is controlled at 30~60℃; when the polyolefin powder is polyethylene powder, the reaction temperature is controlled at 40~70℃; the reaction time is 0.5~1.5 hours in both cases, to obtain polyolefin macromolecular initiator PO-Cl with C-Cl bonds on the surface.
[0010] A further technical solution of the preparation method of the polyolefin graft copolymer with reactive shell described above in this invention may be that, in step S3, the molar ratio of glycidyl methacrylate to butyl acrylate in the mixed monomers is 1:1 to 2:1.
[0011] The present invention relates to the application of the above-described polyolefin graft copolymer with reactive shell in polyolefin composite materials.
[0012] The further technical solution of the above-mentioned application of the present invention is that the polyolefin composite material is made of the following components by weight: 50-90 parts of polyolefin resin, 5-30 parts of inorganic filler, and 5-30 parts of polyolefin graft copolymer with reactive shell.
[0013] A further technical solution of the above-described application of the present invention is that the epoxy groups in the polyolefin graft copolymer with reactive shell in the polyolefin composite material undergo a ring-opening reaction with the hydroxyl groups on the surface of the inorganic filler to form chemical bonds, and the PBA segments form a stress buffer layer with gradually changing modulus between the inorganic filler and the polyolefin resin matrix.
[0014] In a further application of the present invention, the polyolefin resin may be one or a combination of homopolymer polypropylene, copolymer polypropylene, high-density polyethylene, low-density polyethylene, and linear low-density polyethylene; and the inorganic filler may be one or a combination of surface-modified calcium carbonate, talc, mica, silica, magnesium hydroxide, aluminum hydroxide, titanium dioxide, or carbon nanotubes.
[0015] Compared with the prior art, the present invention has the following advantages: Functional Integration and Synergistic Enhancement: This invention integrates a flexible toughening phase (PBA) and a reactive interface layer (GMA-co-BA) into the polyolefin backbone via chemical bonds. When applied to a polyolefin / inorganic filler system, the inner PBA layer directly toughens the matrix, while the outer GMA-co-BA layer is strongly bonded to the filler through epoxy groups. This structure achieves molecular-level synergy between toughening and interface reinforcement, resulting in a significant increase in both the impact strength and tensile strength of the composite material. Unique Interface Buffer Layer: The structure, with its increasing modulus from the inside out, forms an ideal stress buffer and transfer transition zone between the rigid filler and the flexible polymer matrix, efficiently dissipating impact energy and inhibiting interface debonding and crack propagation. Reinforcing Effect: The inorganic filler, anchored to the outer GMA-co-BA layer via chemical bonds, serves as a physical crosslinking point for the flexible PBA segments, limiting excessive slippage. This, in addition to imparting high toughness, significantly improves the strength, modulus, and heat resistance of the composite material, achieving in-situ reinforcement of the rubber phase.
[0016] The core of this invention lies in the chlorination of the polyolefin backbone and the subsequent ATRP grafting process. This process is applicable not only to polypropylene (PP) but also to polyethylene (PE). Due to the low surface energy and difficulty in polarization of PE, traditional compatibilizers have limited modification effects. This invention implants toughening and compatibilizing functions into the PE system through chemical bonding, significantly improving the bonding strength of the PE / filler interface. The flexible segments of PBA have good compatibility with the non-polar polyolefin matrix, and the GMA-co-BA outer layer anchors the filler through chemical reaction. This dual mechanism of "like-like compatibility" and "chemical bonding" enables this compatibilizer to exhibit excellent interface modification effects in polyolefin composites such as polypropylene and polyethylene, and has broad industrial application value. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of the molecular structure of the polyolefin graft copolymer PO-g-(PBA-g-(GMA-co-BA)) of the present invention. Figure 2 This is a schematic diagram illustrating the structure and mechanism of action of the high-toughness, high-strength polyolefin composite material of the present invention. Detailed Implementation
[0018] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments, but the scope of protection of the present invention is not limited to the following embodiments. This embodiment demonstrates the integrated online process of the present invention, aiming to clarify the proportions, process steps, and parameters of each key component in the modified liquid. In actual industrial production, it is necessary to scale up according to the production line scale, impregnation tank volume, and processing throughput.
[0019] Example 1: Preparation of polypropylene macromolecular initiator PP-Cl Take 200g of PP powder and 400mL of deionized water in a 1000mL three-necked flask, and sonicate for 15 minutes to ensure thorough dispersion of the PP powder. Add a calculated amount of NaClO solution to achieve a concentration of 0.02mol / L in the final reaction volume (approximately 500mL). Slowly adjust the pH of the solution to 5-6 with concentrated hydrochloric acid (HCl), and react at 30℃ under light with stirring for 0.5 hours. After the reaction is complete, filter the reaction mixture to separate the solid product. Wash 2-3 times with deionized water to obtain a white powdery product, PP-Cl, for later use.
[0020] Example 2: Preparation of polypropylene graft copolymer PP-g-(PBA-g-(GMA-co-BA)) PBA flexible inner layer polymerization: In a 500mL three-necked flask, 50.0g of PP-Cl and 200mL of anhydrous cyclohexanone were added. After deoxygenation, 40.0g of purified BA monomer, CuCl / bpy (bipyridine) complex solution, and ascorbic acid (ASA) solution were sequentially injected. The reaction was carried out at 90℃ under N2 protection for 3 hours. GMA-co-BA outer layer polymerization: Maintain the reaction system and add a small amount of ASA to reactivate the catalyst. Inject a mixture of 2.0 g BA monomer and 2.0 g GMA monomer at a uniform rate over 0.5 hours (at this point, the BA:GMA molar ratio is approximately 1:1). After the addition is complete, continue the reaction for 1 hour. Termination and purification: After terminating the reaction, the precipitate was repeatedly washed with methanol until the supernatant was clear. The product was then dried under vacuum to obtain a pale yellow solid. Gravimetric analysis showed that the total grafting rate of the product in this example was approximately 65% (based on the mass of PP-Cl), indicating good grafting efficiency.
[0021] Example 3: Preparation and performance testing of high-performance PP / nano-CaCO3 composite materials Functional masterbatch preparation: PP-g-(PBA-g-(GMA-co-BA)) : nano-CaCO3 = 60:40 by mass, with the addition of 0.3% antioxidant B215, followed by high-speed mixing, melt extrusion granulation to obtain the functional masterbatch; Composite material preparation: The above masterbatch and matrix PP resin were mixed at a mass ratio of 1:1 to make the final composite material contain 20wt% nano-CaCO3 and 30wt% PP-g-(PBA-g-(GMA-co-BA)). Standard test specimens were obtained by melt blending and injection molding.
[0022] Performance testing: Tested according to national standards. Notched impact strength is tested according to GB / T 1843-2008, tensile strength according to GB / T 1040.2-2006, flexural modulus according to GB / T 9341-2008, and elongation at break according to GB / T 1040.2-2006.
[0023] Comparative Example 1: A composite material was prepared using a traditional quaternary system: PP / POE (15%) / nano-CaCO3 (20%) / PP-g-MAH (3%).
[0024] Comparative Example 2: Ternary system without compatibilizer: PP / POE (15%) / nano CaCO3 (20%).
[0025] The performance test results are compared below: Homopolymer PP 4.5 35.0 1.5 Comparative Example 1 12.1 31.5 1.6 Comparative Example 2 8.6 36.8 1.8 Example 3 25.3 41.5 2.0 Results Analysis: As shown in the table, the composite material of Example 3 of this invention exhibits significantly improved notched impact strength, tensile strength, and flexural modulus. This fully demonstrates that this invention, through molecular structure design, successfully solves the technical challenge of simultaneously achieving toughening and reinforcement in traditional modification systems.
[0026] Example 3A: Preparation and Performance Testing of High-Performance PP / Talc Composite Material Functional masterbatch preparation: PP-g-(PBA-g-(GMA-co-BA)) : talc = 60:40 by mass, with the addition of 0.3% antioxidant B215, followed by high-speed mixing, melt extrusion granulation to obtain the functional masterbatch; Composite material preparation: The above masterbatch and matrix PP resin were mixed at a mass ratio of 1:1 to make the final composite material contain 20wt% talc and 30wt% PP-g-(PBA-g-(GMA-co-BA)). Standard test specimens were obtained by melt blending and injection molding. Performance testing: Tests were conducted according to national standards, using the same methods as in Example 3. The performance data of the PP / talc composite material are shown in the table below: Pure PP / Talc 7.7 36.8 1.2 Example 3A 19.4 43.6 2.1 This demonstrates that the graft copolymer provided by the present invention also has excellent interfacial compatibilization and toughening effects for sheet-like inorganic fillers with high hardness and high aspect ratio, and verifies the practicality of the technical solution of using talc powder as an inorganic filler in claim 9.
[0027] Example 4: Preparation of high-performance PE / nano-CaCO3 composite materials Preparation of PE macromolecular initiator PE-Cl: Following the method in Example 1, 200g of high-density polyethylene (HDPE) powder was used instead of PP powder. Considering that PE has high crystallinity and slightly lower reactivity than PP, the optimized chlorination conditions were: reaction temperature 40℃, reaction time 1.5 hours, and the remaining steps were the same as in Example 1, to obtain a white powdery product PE-Cl.
[0028] Preparation of PE graft copolymer PE-g-(PBA-g-(GMA-co-BA)): Following the method in Example 2, CuCl / bpy (bipyridine) was used as the catalyst system, and 50.0 g of PE-Cl was used instead of PP-Cl for the SI-ATRP reaction. Specifically, 50.0 g of BA monomer was added for PBA inner-layer polymerization (90°C, 6 hours), followed by the injection of a mixture of 2.0 g of BA and 4.0 g of GMA over 0.5 hours, and the reaction was carried out for 1 hour to obtain the target product. The total grafting rate was determined to be approximately 100%.
[0029] Composite material preparation: The mixture was prepared by mixing PE-g-(PBA-g-(GMA-co-BA)) : nano-CaCO3 at a mass ratio of 60:40, adding 0.3% antioxidant B215, followed by high-speed mixing, melt extrusion granulation, and then mixing with HDPE matrix at a mass ratio of 1:1. The final composite material contained 20wt% nano-CaCO3 and 30wt% graft copolymer. Standard test specimens were obtained by melt blending and injection molding.
[0030] Performance verification: Tests were conducted according to national standards. Notched impact strength was tested according to GB / T 1843-2008, tensile strength according to GB / T 1040.2-2006, flexural modulus according to GB / T 9341-2008, and elongation at break according to GB / T 1040.2-2006.
[0031] Comparative Example 3: HDPE : stearic acid activated nano-CaCO3 at a mass ratio of 80:20, with the addition of 0.3% antioxidant B215, was mixed at high speed, melt extruded and granulated, and then injection molded.
[0032] Pure HDPE 8.5 22.0 1.1 Comparative Example 3 7.9 24.5 1.2 Example 4 21.3 25.3 1.38 Compared with Comparative Example 3, the notched impact strength of the PE composite material in Example 4 was significantly increased from 7.9 kJ / m² to 21.3 kJ / m²; at the same time, the tensile strength increased from 24.5 MPa to 25.3 MPa, and the flexural modulus increased from 1.2 GPa to 1.38 GPa, achieving a synergy of high toughness and high modulus.
Claims
1. A polyolefin graft copolymer with a reactive shell, characterized in that, It has the following general structural formula: PO-g-{PBA-g-(GMA-co-BA)}; wherein, PO is a polyolefin backbone, one or a combination of polypropylene and polyethylene; PBA is a polybutyl acrylate segment, constituting the flexible inner layer of the shell; GMA-co-BA is a random copolymer segment of glycidyl methacrylate and butyl acrylate, constituting the reactive outer layer of the shell; from PBA segment to GMA-co-BA segment, the relative content of glycidyl methacrylate structural units gradually increases, so that the modulus of the shell shows a gradient change that gradually increases from the inside to the outside; based on 100 parts by mass of the polyolefin backbone, the total grafting rate of PBA segment and GMA-co-BA segment is 50~100 parts by mass.
2. The polyolefin graft copolymer with a reactive shell according to claim 1, characterized in that, The mass ratio of the PBA segment to the GMA-co-BA segment is 5:1 to 10:
1.
3. The polyolefin graft copolymer with a reactive shell according to claim 1, characterized in that, In the GMA-co-BA segment, the molar ratio of glycidyl methacrylate to butyl acrylate is 2:1 to 1:
1.
4. A method for preparing a polyolefin graft copolymer with a reactive shell as described in any one of claims 1-3, characterized in that, Includes the following steps: S1. Preparation of PO-Cl, a polyolefin macromolecular initiator with C-Cl bonds on its surface; S2. Using the PO-Cl as an initiator, a surface-initiated atom transfer radical polymerization method is adopted to first initiate the butyl acrylate monomer to undergo a first polymerization reaction to form PBA segments; S3. Without terminating the reaction system, a mixture of butyl acrylate and glycidyl methacrylate monomers is added to the system to carry out a second polymerization reaction, thereby forming GMA-co-BA copolymer segments at the ends of the PBA segments to obtain a polyolefin graft copolymer with a reactive shell.
5. The method for preparing the polyolefin graft copolymer with a reactive shell according to claim 4, characterized in that, The method for preparing the polyolefin macromolecular initiator PO-Cl with C-Cl bonds on its surface is as follows: Under acidic conditions, sodium hypochlorite is used to react with polyolefin powder in a chlorination reaction; when the polyolefin powder is polypropylene powder, the reaction temperature is controlled at 30~60℃; when the polyolefin powder is polyethylene powder, the reaction temperature is controlled at 40~70℃; the reaction time is 0.5~1.5 hours in both cases, to obtain the polyolefin macromolecular initiator PO-Cl with C-Cl bonds on its surface.
6. The method for preparing the polyolefin graft copolymer with a reactive shell according to claim 4, characterized in that, In step S3, the molar ratio of glycidyl methacrylate to butyl acrylate in the mixed monomers is 1:1 to 2:
1.
7. The use of a polyolefin graft copolymer with a reactive shell as described in any one of claims 1-3 in polyolefin composites.
8. The application according to claim 7, characterized in that, The polyolefin composite material is made of the following components by weight: 50-90 parts of polyolefin resin, 5-30 parts of inorganic filler, and 5-30 parts of polyolefin graft copolymer with reactive shell.
9. The application according to claim 8, characterized in that, In the polyolefin composite material, the epoxy groups in the polyolefin graft copolymer with a reactive shell undergo a ring-opening reaction with the hydroxyl groups on the surface of the inorganic filler to form chemical bonds, and the PBA segments form a stress buffer layer with gradually changing modulus between the inorganic filler and the polyolefin resin matrix.
10. The application according to claim 8, characterized in that, The polyolefin resin is one or a combination of homopolymer polypropylene, copolymer polypropylene, high-density polyethylene, low-density polyethylene, and linear low-density polyethylene; the inorganic filler is one or a combination of surface-modified calcium carbonate, talc, mica, silica, magnesium hydroxide, aluminum hydroxide, titanium dioxide, or carbon nanotubes.